From Environmental Management Systems to Airport Environmental Performance: A Model Assessment - PARASCHI, Elen Paraskevi; POULAKI, Ioulia; PAPAGEORGIOU, Athina (Journal of Environmental Management and Tourism; Vol 13 No 3 (2022): JEMT, Volume XIII, Issue 3(59), Summer 2022, 2022)
In the last decades, aviation industry has expressed an increasing interest in the application of environmental management systems (EMSs). Many scholars have examined the environmental impact of the airports’ operations, but few have studied the management practices used to develop airport environmental policies. This study aims to contribute to academic and managerial knowledge by exploring and evaluating the application of EMS in the largest Greek airport, namely Athens International Airport (AIA). To achieve this goal, a qualitative case study was conducted in every dimension and aspect of AIA’s Environmental Management System. Subsequently, a new Airport Environmental Performance Model (AEP) was built combining the case study results with the most common benchmarking models proposed in the literature. This research enhances the understanding about the airport environmental management and offers best-practice insights to scholars and aviation professionals altogether, proposing the new AEP.